Influence of operational variables in multi-particulate delayed release systems for colon-targeted drug delivery of celecoxib using extrusion spheronization - Sinha, V R; Aggarwal, A; Srivastava, S (Asian Journal of Pharmaceutics (AJP), 2014)
The present research was aimed to formulate and evaluate pH and time-dependent multiparticulate systems for colon-targeted drug delivery of celecoxib (CXB) with maximum drug absorption, reduced peak plasma fluctuations, and minimum potential side effects. Multiple unit delayed release systems of the drug in MCC (Avicel® PH-102) grade were prepared using polymethacrylate polymers (Eudragit® L-100 and RSPO) as a granulating binder by the extrusion- spheronization technique and characterized for their shape, size, size distribution, friability, density, and moisture content. In vitro release studies were performed in 0.1N HCl, for first 2 h then further performed in phosphate buffer (pH 6.8) for 24 h. The resulting pellets were prepared by extrusion spheronization using different grades of polymethacrylate polymers as a granulating binder, showing a substantial decrease in drug release in initial 5 h (16.28-16.7%) and releasing most of the drug in 12-24 h. The geometric and arithmetic mean diameter ranged from (490 to 780 μm) and (636 to 734 μm), respectively. The minimum to maximum range for circularity, elongation and rectangle were found to be (0.847±0.009 to0.965±0.078), (1.036±0.057 to 1.185±0.023), and (0.724±0.041 to 0.791±0.047) respectively showing the proper shape and size of the pellets. The content of CXB in the prepared pellets was observed between 98.70 and 99.47% justifying the uniform drug distribution. The in vitro dissolution studies showed that the retardant effect in initial 5 h and most of the drug release in 24 h depended on the ratio and concentration of different grades of methacrylate polymers used in the formulation. CXB-loaded MUPS prepared by the extrusion-spheronization technique using polymethacrylate polymers showed immense potential for colon-specific drug delivery of the drug.